Unravelling the trophic interaction between a parasitic barnacle (Anelasma squalicola) and its host Southern lanternshark (Etmopterus granulosus) using stable isotopes. Issue 14 (9th December 2022) - Sabadel, A. J. M.; Cresson, P.; Finucci, B.; Bennett, J.
Abstract: Abstract: The parasitic barnacle, Anelasma squalicola, is a rare and evolutionary fascinating organism. Unlike most other filter-feeding barnacles, A. squalicola has evolved the capability to uptake nutrient from its host, exclusively parasitizing deepwater sharks of the families Etmopteridae and Pentanchidae. The physiological mechanisms involved in the uptake of nutrients from its host are not yet known. Using stable isotopes and elemental compositions, we followed the fate of nitrogen, carbon and sulphur through various tissues of A. squalicola and its host, the Southern lanternshark Etmopterus granulosus, to better understand the trophic relationship between parasite and host. Like most marine parasites, A. squalicola is lipid-rich and clear differences were found in the stable isotope ratios between barnacle organs. It is evident that the deployment of a system of 'rootlets', which merge with host tissues, allows A. squalicola to draw nutrients from its host. Through this system, proteins are then rerouted to the exterior structural tissues of A. squalicola while lipids are used for maintenance and egg synthesis. The nutrient requirement of A. squalicola was found to change from protein-rich to lipid-rich between its early development stage and its definitive size.